2019
DOI: 10.1021/acs.inorgchem.8b02820
|View full text |Cite
|
Sign up to set email alerts
|

Trapping CS22– and S32– between Two Ytterbium Formamidinates

Abstract: Treatment of [Yb II (DippForm) 2 (thf) n ] (n = 2 (1aYb), n = 1 (1bYb); DippForm = N,N′-bis(2,6-diisopropylphenyl)f o r m a m i d i n a t e ), w i t h e i t h e r e x c e s s C S 2 o r S 8 g i v e s [Yb III 2 (DippForm) 4 (CS 2 )] (3) and [Yb III 2 (DippForm) 4 (S 2 ) 0.5 /(S 3 ) 0.5 ] (4) respectively. 3 is a new addition to an exclusive class of compounds containing the CS 2 2− dianion, and 4 is the first crystallographically characterized example of a rare-earth trisulfide complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…By using different electronic and steric environments around divalent lanthanide elements, a different reactivity can be achieved with a same substrate. [37][38][39][40][41][42][43][44][45] 42 In addition, activation of white phosphorous and yellow arsenic by [(DippForm) 2 Sm II (thf ) 2 ] led to the formation of [{(DippForm) 2 Sm III } 2 (μ-η 4 -Pn 4 )] (Pn = P, As). 43 These products contrast with the cage-type molecules [{Cp* 2 Sm III } 4 (Pn) 8 ] (Pn = P, 37 As, 44 and Sb 47 ) that were obtained by reaction of [Cp* 2 Sm II ] with white phosphorous, nanoscale arsenic, and nanoscale antimony, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…By using different electronic and steric environments around divalent lanthanide elements, a different reactivity can be achieved with a same substrate. [37][38][39][40][41][42][43][44][45] 42 In addition, activation of white phosphorous and yellow arsenic by [(DippForm) 2 Sm II (thf ) 2 ] led to the formation of [{(DippForm) 2 Sm III } 2 (μ-η 4 -Pn 4 )] (Pn = P, As). 43 These products contrast with the cage-type molecules [{Cp* 2 Sm III } 4 (Pn) 8 ] (Pn = P, 37 As, 44 and Sb 47 ) that were obtained by reaction of [Cp* 2 Sm II ] with white phosphorous, nanoscale arsenic, and nanoscale antimony, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the reactiono fL n II with sulfur can yield dinuclear sulfide, disulfide, trisulfide and polysulfide complexes or fascinating sulfide-bridged cluster compounds. [9,19] The reduction of CS 2 to acetylenedithiolate is unprecedented both in f-and d-block metal chemistry.T herefore, DFT calculations (B3PW91) werecarriedout to gain insights into this peculiar reactivity (Figure 4).The reactionb egins with the double reductiono fC S 2 by complex 1,y ielding the dinuclear "key intermediate" (complex 3). This step was found to be exothermic by 22.4 kcal mol À1 as foundi no ther reactions.…”
Section: àmentioning
confidence: 99%
“…CS 2 activation by lanthanide ions has so far resulted in CS 2 disproportionation or reductive C−S or C−C coupling to afford thiocarbonate, thiooxalate and thioformyl carbonotrithioate [(SCSCS 2 ) 2− ] respectively . Very recently the first example of a rare CS 2 2− dianion trapped between two Yb III ions has also been reported …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations